Reliability Evaluation of Photovoltaic System Based on Time Varying Factors - Lin ZHU; Tao HAN; Yinghua DONG; Yabo YU; Yulong XUE (Zhongguo dianli)
With the large-scale development of photovoltaic (PV) generations, the reliability level of PV stations has attracted more and more attention. A reliability evaluation method of photovoltaic generation is proposed based on time-varying factors. By analyzing the operation mechanism of PV generation system, the component failure mode and its impact on output power, a probabilistic model of system output power is proposed and the reliability evaluation indices of PV system are established, and a six-state space model of PV system is constructed as well. Based on the sequential Monte Carlo method, the operational reliability of a 50 MW PV station is evaluated with consideration the climate conditions, component aging and radiations. The simulation results show that the proposed model and indices can effectively reflect the actual operation state, output level and fault conditions of the system, which can provide support for the operation and maintenance of PV stations.